Corporate tax Reform and foreign direct investment in Germany: evidence from firm-level data - Johannes Becker; Clemens Fuest; Thomas Hemmelgarn (Center for Economic Studies and ifo Institute (CESifo), 2006)
Does the reduction of the effective tax burden on corporations trigger foreign direct investment? We take the German tax reform of 2000 as a natural experiment in order to isolate the impact of corporate taxation on the investment of foreign-held affiliates in Germany. We do so by exploiting the very rich MiDi data base from the Deutsche Bundesbank. Although we deliberately choose an approach which is likely to underestimate the tax effects on investment we find significant evidence that the tax reduction had the intended effect of - ceteris paribus - fostering inward direct investment. We find an elasticity of inward foreign direct investment with respect to the effective marginal tax rate of -0.7. We repeat the analysis for different subgroups and find high degrees of heterogeneity. Our results do not allow to decide whether the model of discrete investment choices or the model of marginal adjustment of the capital stock performs better in explaining the investment data.
Keywords: H25; H21; 330